Low Threshold Room Temperature Polariton Lasing from Fluorene‐Based Oligomers. Issue 8 (17th June 2021) - Wei, Mengjie; Ruseckas, Arvydas; Mai, Van T. N.; Shukla, Atul; Allison, Ilene; Lo, Shih‐Chun; Namdas, Ebinazar B.; Turnbull, Graham A.; Samuel, Ifor D. W.
Abstract: Organic semiconductors possessing tightly bound Frenkel excitons are known to be attractive candidates for demonstrating polariton lasing at room temperature. As polariton lasing can occur without inversion, it is a potential route to very low threshold coherent light sources. However, so far, the thresholds of organic polariton lasers have generally been much higher than those of organic photon lasers. Here this problem has been addressed by investigating two new organic molecules with a structure combining fluorene and carbazole groups. The materials are readily deposited from solution and exhibit high photoluminescence quantum yields, high absorption coefficients, and large radiative decay rates in neat films. Room temperature polariton lasing is realized in both materials with incident thresholds of 13.5 and 9.7 µJ cm −2, corresponding to absorbed thresholds of 3.3 and 2.2 µJ cm −2, respectively. These are the lowest values reported to date for polariton lasing in organic semiconductor materials, and approach typical values for organic photon lasers. The step‐like power dependent blue‐shift of polariton modes indicates an interplay between different depletion channels of the exciton reservoir. This work brings practical room temperature polaritonic devices and future realization of electrically driven polariton lasers a step closer. Abstract : Room temperature polariton lasing is demonstrated in two fluorene‐based oligomers at record low absorbed thresholds of 3.3 and 2.2 µJ cm −2 . By combining favorable material properties and optimal microcavity configuration, this work brings the polariton lasing threshold down to the typical order of magnitude for organic photon lasers and paves the way to realization of electrically driven polariton lasers.